Party studies. volume 2 underground clubs, parallel structures and second cultures - Aguado, Victor; Del Buey, Ramon; Labelle, Brandon (Berlin Errant Bodies Press, 2024)
In what ways does the underground operate as a key imaginary for subcultural expression? From basement gatherings to hidden clubs to the passing of messages, how does secrecy lend to manifestations of partying and the drive or necessity of alternative communal life? Is clandestinity, and gestures of exit, necessary for working against a given social order? Pursuing these lines of inquiry, party studies vol. 2 comprises essays, documentation, and poetic notes on secrecy as a key axis around which experimental ang non-normative modes of being-in-common take place. Continuing from vol. 1 on the topics of home gatherings and house parties, the second volume elaborates understandings of the party by considering the hidden, the invisible, and the underground as material and imaginary forces, where partying is not only festive and excessive, but manifests in forms of social and political organizing, cultural and subcultural conversation, the maintenance of safe spaces and the building of parallel structures against established institutional forms. As such, the party is underscored as the collective enactments and configurations often made in support of ontological invention and which gain traction by way of heterotopian and interstitial occupations.
Donated by Prof. Dayang Nirvana Magdalena Yraola
Keywords: Parties; Social skills; Secrecy; Subculture -- Expressions